Current state in the development of candidate therapeutic HPV vaccines. (2nd August 2016) - Yang, Andrew; Jeang, Jessica; Cheng, Kevin; Cheng, Ting; Yang, Benjamin; Wu, T.-C.; Hung, Chien-Fu
ABSTRACT: The identification of human papillomavirus (HPV) as an etiological factor for HPV-associated malignancies creates the opportunity to control these cancers through vaccination. Currently, available preventive HPV vaccines have not yet demonstrated strong evidences for therapeutic effects against established HPV infections and lesions. Furthermore, HPV infections remain extremely common. Thus, there is urgent need for therapeutic vaccines to treat existing HPV infections and HPV-associated diseases. Therapeutic vaccines differ from preventive vaccines in that they are aimed at generating cell-mediated immunity rather than neutralizing antibodies. The HPV-encoded early proteins, especially oncoproteins E6 and E7, form ideal targets for therapeutic HPV vaccines since they are consistently expressed in HPV-associated malignancies and precancerous lesions, playing crucial roles in the generation and maintenance of HPV-associated disease. Our review will cover various therapeutic vaccines in development for the treatment of HPV-associated lesions and cancers. Furthermore, we review strategies to enhance vaccine efficacy and the latest clinical trials on therapeutic HPV vaccines.